Peran Dunia Usaha dan Dunia Industri Dalam Menumbuhkan Pebisnis Baru di Era Revolusi Industri 4.0 - Aziz, Muh. Abdul (PT. Alahyan Publisher Sukabumi, 2023)
The webinar on the role of the business world and the industrial world in growing new business people in the era of the Industrial Revolution 4.0 is one solution to the problems faced, namely how to grow new business people in the Industrial Revolution 4.0. The purpose of this webinar activity is to increase the understanding of students, students, and the general public regarding the role of DUDI in growing new business people in the era of the Industrial Revolution 4.0. The method of implementing this activity starts with preparation, webinars, and evaluation using the Zoom meeting application for all participants. The partner in this webinar activity is the Retail Management Study Program of Muhammadiyah Sukabumi University. The evaluation was carried out by giving questionnaires to webinar participants before and after delivering the material, where the result was that participants' understanding increased by 42.5%.